2015
DOI: 10.1016/j.foodchem.2014.07.152
|View full text |Cite
|
Sign up to set email alerts
|

Diversity for chemical composition in a collection of different varietal types of tree tomato (Solanum betaceum Cav.), an Andean exotic fruit

Abstract: We evaluated 23 tree tomato (Solanum betaceum) accessions from five cultivar groups 24 and one wild relative (S. cajanumense) for 26 composition traits. For all traits we found 25 highly significant differences (P<0.001) among the materials studied. The high diversity 26 found within S. betaceum for composition traits was matched by a high diversity within 27 each of the cultivar groups. We found that sucrose and citric acid were the most 28 important soluble sugar and organic acid, respectively, in tree tomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 29 publications
7
50
3
6
Order By: Relevance
“…A linear relationship was observed between the antioxidant effect of water extract and its TPC which indicates that high content of phenols confers greater antioxidant activity. This conclusion was also agreed by a number of previous studies which found that plants extracts rich in phenols tend to show high antioxidant property (Acosta‐Quezada et al, ; Barbouchi, Elamrani, El Idrissi, & Choukrad, ; Islam, Yu, & Xu, ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A linear relationship was observed between the antioxidant effect of water extract and its TPC which indicates that high content of phenols confers greater antioxidant activity. This conclusion was also agreed by a number of previous studies which found that plants extracts rich in phenols tend to show high antioxidant property (Acosta‐Quezada et al, ; Barbouchi, Elamrani, El Idrissi, & Choukrad, ; Islam, Yu, & Xu, ).…”
Section: Resultssupporting
confidence: 90%
“…Increased reactive oxygen/nitrogen species (ROS/RNS) have long been associated to oxidative damages to macromolecules, including nucleic acids, proteins and lipids (Uttara, Singh, Zamboni, & Mahajan, 2009). In particular, lipid peroxidation can be considered as a key factor in colon inflammation (Achitei et al, 2013). To this regard, the evaluation of colon nitrite level is a validated tool to measure the synthesis of NO, which is deeply involved in colon tissue damage (Goggins et al, 2001).…”
Section: Pharmacological Studiesmentioning
confidence: 99%
“…Furthermore, the trend observed in the current study revealed that the aqueous extracts of the tested plants showed the highest antioxidant activity in most assays, which conforms with the highest content of phenolics and flavonoids. In fact, some previous studies have proven that the antioxidant activity of plant extracts is positively correlated with their polyphenolic content …”
Section: Resultsmentioning
confidence: 99%
“…However, the expansion of this crop is limited by factors such as the lack of clear differentiation among varieties, low fruit quality (heterogeneity and phytosanitary problems), the use of inappropriate varieties or replacement of local varieties by materials from other origins not adapted [64]. Some works studying genetic diversity have indicated the existence of considerable variability and that it is possible to select materials with characteristics more suitable for fruit market [19,[64][65][66]; however, more investigations related to its conservation and genetic improvement are needed [64,67].…”
Section: Agronomic Aspectsmentioning
confidence: 99%
“…Nevertheless, while health-related properties and chemical composition of berries commonly found in North America and Europe have been widely explored; those natives from South America need more information. Several scientific reports have pointed out the therapeutic potential of certain plants and foods from this area, for instance Rubus glaucus B., Physalis peruviana L. and Solanum betaceum C. are among the relevant ones [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%